Web-Based Sasak Encyclopedia Application as an Effort to Preserve the Sasak Language - Samsu, L M; Saiful, Muhammad (Journal of Applied Intelligent System, 2023)
The Sasak tribe is an indigenous tribe that inhabits the island of Lombok which has a rich cultural history. In a sociolinguistic approach, the Sasak language has a 3-level pyramid variation which represents low, medium and high. The status identities of speakers who use it are you (low), aside (middle), pelinggih (high). Basically the speech level of the Sasak language resembles the speech level of the Javanese language which is in the form of a pyramid of 3 levels: Full, Middle, Krama. At the highest level, Krama uses Soft Sasak Language (Base Alus). Based on observations, researchers feel a lack of understanding of the community in using the Sasak language, especially Basis Alus, often hearing Sasak sentences mixed with other languages emphasizes the decline in awareness and cultural literacy of the Sasak people. In this case, the researchers focused on analyzing the Sasak language by preparing instruments to developing an android-based Sasak Encyclopedia website & application which became a place of reference in learning and developing the Sasak language. The researcher's ultimate goal is to create a new movement to jointly protect and care for Sasak culture. Because cultured people will like culture.